Dysregulated Reward‐Inhibition Network Interactions During Food‐Cue Exposure in Disinhibited Restrained Eaters: Evidence From Task‐Based PPI and DCM. - Wang, Shaorui; Xiao, Mingyue; Han, Jinfeng; Cui, Yicen; Chen, Hong (International Journal of Eating Disorders, 2025)
Objective: Disinhibited restrained eaters are particularly susceptible to dietary lapses and are at increased risk for the onset of eating disorders. To elucidate the neural mechanisms underlying this vulnerability, the present study examined interactions between the reward and inhibition systems during food cue exposure. Method: Sixty female restrained eaters (aged 17–26 years) completed a task‐based fMRI paradigm involving food and neutral cues under satiety. Participants were grouped by disinhibition level based on the Dutch Eating Behavior Questionnaire. Psychophysiological interaction (PPI) and dynamic causal modeling (DCM) were used to assess task‐modulated functional and effective connectivity. Disinhibited eating was behaviorally assessed via the eating in the absence of hunger (EAH) paradigm. Results: Disinhibited restrained eaters showed weaker functional connectivity between reward (e.g., putamen, globus pallidus [GP]) and inhibition (e.g., inferior frontal gyrus [IFG]) regions, as well as reduced excitatory modulation from reward to inhibition regions (GP → inferior parietal lobule [IPL]). This diminished effective connectivity significantly predicted greater caloric intake during the EAH task. Discussion: The study revealed a convergence of reduced functional and effective connectivity between the reward and inhibition systems in disinhibited restrained eaters. Both the synchrony and directional influence between these systems were weakened during food cue exposure. Notably, diminished excitatory modulation along the GP → IPL pathway significantly predicted greater caloric intake, suggesting this pathway may serve as a neural marker of vulnerability to disinhibited eating and dietary lapses.